2016
DOI: 10.1590/1807-1929/agriambi.v20n1p16-21
|View full text |Cite
|
Sign up to set email alerts
|

Soybean nutritional status and seed physiological quality with swine wastewater

Abstract: Swine wastewater application is a practice that can become viable in agriculture, for minimizing fertilization costs and improving soil conditions. Therefore, it is essential to establish criteria that define appropriate application doses from the agronomic and environmental perspectives. The objective of this study was to evaluate the effects of swine wastewater doses associated with mineral fertilization on soybean nutritional status and physiological quality of seed. The experiment was conducted in the agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Several studies have reported the impact of wastewater disposal on soil Rosa et al, 2017), leachate (Prior et al, 2009;Maggi et al, 2011;Lourenzi et al, 2014b), drained (Dal Bosco et al, 2008b;Doblinski et al, 2010;Wang et al, 2013), crops (Kessler et al, 2013a;Kessler et al, 2013b;Passarin et al, 2016;Lourenzi et al, 2014a), and biota (Tessaro et al, 2013;Brooks et al, 2014;Castaldelli et al, 2015;Tessaro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the impact of wastewater disposal on soil Rosa et al, 2017), leachate (Prior et al, 2009;Maggi et al, 2011;Lourenzi et al, 2014b), drained (Dal Bosco et al, 2008b;Doblinski et al, 2010;Wang et al, 2013), crops (Kessler et al, 2013a;Kessler et al, 2013b;Passarin et al, 2016;Lourenzi et al, 2014a), and biota (Tessaro et al, 2013;Brooks et al, 2014;Castaldelli et al, 2015;Tessaro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, there are effects on agricultural crops (Berenger et al, 2008;Kessler et al, 2013a;Kessler et al, 2013b;Gómez-Garrido et al, 2014;Passarin et al, 2016), soil chemical , physical (Oliveira et al, 2015), and biological characteristics (Tessaro et al, 2013;Brooks et al, 2014;Castaldelli et al, 2015;Moura et al, 2016). Besides, there is the leaching (Prior et al, 2009; Corn fertilization using swine wastewater and soil-water environmental quality Eng.…”
Section: Introductionmentioning
confidence: 99%
“…Passarin et al (2016) (Lopes, et al, 2014), valor superior ao encontrado no presente estudo aos 125 dias (2510,5 mg/kg) e >267 dias (837,3 mg/kg), o que indica que a utilização do composto como fertilizante não eleva à níveis tóxicos as quantidades destes minerais no solo.…”
Section: Weber Nc Et Alunclassified